2005
DOI: 10.1111/j.1471-4159.2005.03211.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic gestational treatment with caffeine or theophylline on Group I metabotropic glutamate receptors in maternal and fetal brain

Abstract: Pregnant rats were treated throughout the gestational period with either caffeine or theophylline, and its effect on the metabotropic glutamate receptor (mGluRs) signal transduction pathway was studied in both maternal and fetal brain. In maternal brain, radioligand binding assays showed that chronic treatment with methylxanthines caused a significant decrease in the total number of mGluRs. This decrease was accompanied by an increase in receptor affinity. Immunodetection showed that mGluR 1a and phospholipase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Thus, exposure to caffeine during development can have long-term effects on adenosine receptor expression. Further, the levels of mGluRs are decreased in the fetal brain following caffeine and theophylline treatment [28]. Enduring changes in adenosinergic and glutamatergic receptor expression following perinatal caffeine exposure may contribute to changes in learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, exposure to caffeine during development can have long-term effects on adenosine receptor expression. Further, the levels of mGluRs are decreased in the fetal brain following caffeine and theophylline treatment [28]. Enduring changes in adenosinergic and glutamatergic receptor expression following perinatal caffeine exposure may contribute to changes in learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Leon et al (28) reported that chronic caffeine or theophylline treatment downregulated group I metabotropic glutamate receptors, one of the G protein-coupled membrane-bound receptor superfamily, in both maternal and fetal brains in a rat animal model. In the present study, we found that the maternal caffeine effects on embryonic CV function occurred via adenosine A 2A receptor blockade.…”
mentioning
confidence: 99%
“…Equal loading and even transfer of protein gels was confirmed visually by staining the blot with the reversible dye Ponceau S prior to incubation with antibody. Western blotting was performed as described elsewhere (León et al, 2005a). Immunodetection was carried out by incubating the nitrocellulose membranes with specific polyclonal antibodies (anti‐mGlu 1 receptor, anti‐mGlu 5 receptor, and anti‐αG q/11 ) diluted 1:1,000 and isoenzyme‐specific monoclonal antibody (anti‐PLCβ 1 ) diluted 1:400. β‐Actin antibody (1:5,000) was used as a gel loading control.…”
Section: Methodsmentioning
confidence: 99%
“…Although the cross‐interaction between metabotropic glutamate and adenosine receptors has been described from several in vitro approaches, including cerebrocortical nerve terminals (Vazquez et al, 1995), hippocampal slices (de Mendonca and Ribeiro, 1997), and cultured cells (Ogata et al, 1996; Cartmell et al, 1998; Toms and Roberts, 1999), little is known about cross‐talk between these receptors after chronic in vivo activation of one of these signal transduction pathways. Previously, we have described that oral administration of caffeine or theophylline, antagonists of adenosine A 1 receptors, to pregnant rats down‐regulates several mGlu/PLC transduction pathway components in both maternal and fetal brain, causing a loss of receptor responsiveness only in maternal brain (León et al, 2005a). On the other hand, R‐phenylisopropyladenosine (R‐PIA) chronically administered to male rats during 6 days caused a significant increase in the mGlu/PLC pathway from the brain (Albasanz et al, 2002).…”
mentioning
confidence: 99%